Imagining new linkages in the Anthropocene:other correspondences and stories between larch forest, shingles and humans (Revista LIDER, 2021)
The article proposes, through an exercise of imagination, new possibilities of understanding and relations between human life and the other-than-human. The deep crisis in which we are immersed, conceptualized in terms of the Anthropocene, requires a reflection on life. This reflection can no longer be just humanistic or scientific-technical, instead it needs a dialogue with other epistemologies in order to reinterpret the materialities and links that build human life on the planet. We select the larch tile to study those links. The larch tile, which comes from the forests of the Cordillera Pelada and remaining in southern Chile is narrated in its multiple interactions and it leads us to a broader thinking, feeling, and knowing. In other words, to a different meaning of the territory. This reading helps us to redirect the present time and to face the socio-environmental crisis in the best possible way. Or, at least, in a way where the imagination and the creativity might play a fundamental role in the plot that we called coexistence. Two stories are presented to enrich the theoretically discussed, in order to see the imagination materialize, and stimulate other practices and new understandings of multispecies alliances.